Preoperative plasma level of endoglin as a predictor for disease outcomes after radical cystectomy for nonmetastatic urothelial carcinoma of the bladder - Laukhtina, Ekaterina; Schuettfort, Victor M; D'Andrea, David; Pradere, Benjamin; Mori, Keiichiro; Quhal, Fahad; Sari Motlagh, Reza; Mostafaei, Hadi; Katayama, Satoshi; Grossmann, Nico С; Rajwa, Pawel; Zeinler, Flora; et al. (Molecular carcinogenesis, 2022)
Elevated preoperative plasma level of endoglin has been associated with worse oncologic outcomes in various malignancies. The present large-scale study aimed to determine the predictive and prognostic values of preoperative endoglin with regard to clinicopathologic and survival outcomes in patients treated with radical cystectomy (RC) for nonmetastatic urothelial carcinoma of the bladder (UCB). We prospectively collected preoperative blood samples from 1036 consecutive patients treated with RC for UCB. Logistic and Cox regression analyses were undertaken to assess the correlation of endoglin levels with pathologic and survival outcomes, respectively. The AUC and C-index were used to assess the discrimination. Patients with adverse pathologic features had significantly higher median preoperative endoglin plasma levels than their counterparts. Higher preoperative endoglin level was independently associated with an increased risk for lymph node metastasis, ≥pT3 disease, and nonorgan confined disease (NOCD; all p < 0.001). Plasma endoglin level was also independently associated with cancer-specific and overall survival in both pre- and postoperative models (all p < 0.05), as well as with recurrence-free survival (RFS) in the preoperative model (p < 0.001). The addition of endoglin to the preoperative standard model improved its discrimination for prediction of lymph node metastasis, ≥pT3 disease, NOCD, and RFS (differential increases in C-indices: 10%, 5%, 5.8%, and 4%, respectively). Preoperative plasma endoglin is associated with features of biologically and clinically aggressive UCB as well as survival outcomes. Therefore, it seems to hold the potential of identifying UCB patients who may benefit from intensified therapy in addition to RC such as extended lymphadenectomy or/and preoperative systemic therapy.
Keywords: regulace genové exprese u nádorů; Humans; biomarker; endoglin; lidé středního věku; analýza přežití; karcinom z přechodných buněk; Endoglin; předoperační období; Biomarkers, Tumor; Female; Aged; výsledek terapie; Cystectomy; senioři; lidé; Preoperative Period; Lymph Node Excision; Survival Analysis; nádorové biomarkery; staging nádorů; ženské pohlaví; Male; nádory močového měchýře; Middle Aged; prognóza; Carcinoma, Transitional Cell; Treatment Outcome; lymfadenektomie; Neoplasm Staging; cystektomie; mužské pohlaví; prospektivní studie; Gene Expression Regulation, Neoplastic; Urinary Bladder Neoplasms; bladder cancer; radical cystectomy; Prognosis; Prospective Studies